Thyroid Dysfunction as a Predictive Indicator in Camrelizumab of Advanced Esophageal Squamous Cell Carcinoma - Ying Chen; Lei Zhuang; Danhong Zhang; Xianghui Du; Liming Sheng (Journal of Immunology Research)
Thyroid dysfunction (TD) induced by programmed death-1 (PD-1) or programmed cell death-ligand 1 (PD-L1) immune checkpoint inhibitors (ICIs) has been widely reported. However, the effects of ICI-induced TD on the survival of patients with esophageal squamous cell carcinoma (ESCC) have not been described. Herein, a retrospective study was conducted, which 82 patients with advanced metastatic or recurrent ESCC treated with camrelizumab were enrolled. Twenty patients (24.4%) experienced TD during camrelizumab treatment with or without chemotherapy. The median onset time of TD was 1.7 months. The incidence of TD was 35.6% in patients who previously received thoracic radiotherapy versus 10.8% in patients who did not (P =0.009). Patients with TD had significantly longer median progression-free survival (5.5 months vs 3.5 months, P =0.035) and overall survival (26.7 months vs 11.5 months, P <0.001). TD is frequently observed in ESCC patients treated with camrelizumab and especially in patients who received radiotherapy previously. ESCC patients with TD during ICIs treatment often have better prognosis.